Voices and visions: Navigating the landscape of sexual, reproductive, and maternal health and rights in Latin America and the Caribbean: A stakeholder mapping and analysis - Sofia Pirsch; Denise Zavala; Mabel Berrueta; María Belizán; Juan Pedro Alonso; Sandra Formia; Jamile Ballivian; Miluska Ramirez-Rodríguez; Maisa Havela; Gabriela Perrota; Analía López; Cintia Cejas; et al. (Global Public Health)
This article presents the results of a mapping and analysis of key stakeholders operating in the field of Sexual, Reproductive, and Maternal Health and Rights (SRMHR) who are involved in the entitlement of health rights and access to health services for women, adolescents, LGBTQI+ individuals, migrants, indigenous people, Afro-descendants, and people with disabilities in Latin America and the Caribbean. Our study focuses on Argentina, Colombia, Guatemala, Guyana, Jamaica, Mexico, and Peru. The primary objective was to identify and comprehensively categorise the activities undertaken by them, since their actions shape, and promote or hinder the SRMHR political agenda in the region. The findings of this mapping can be useful in contributing to the development of public policy strategies.